2020
DOI: 10.5306/wjco.v11.i8.528
|View full text |Cite
|
Sign up to set email alerts
|

B-cell lymphoma-2 inhibition and resistance in acute myeloid leukemia

Abstract: Spurred by better understanding of disease biology, improvements in molecular diagnostics, and the development of targeted therapies, the treatment of acute myeloid leukemia (AML) has undergone significant evolution in recent years. Arguably, the most exciting shift has come from the success of treatment with the B-cell lymphoma-2 inhibitor venetoclax. When given in combination with a hypomethylating agent or low dose cytarabine, venetoclax demonstrates high response rates, some of which are durable. In spite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 90 publications
(91 reference statements)
1
1
0
Order By: Relevance
“… 3 Finally, although the majority of newly diagnosed patients respond to venetoclax-based combinations, the median duration of response may only be approximately 12 months, which necessitates an understanding of how resistance evolves and how this can be targeted. 23 In our study, we also found that four of 10 CR/CRi patients relapsed, and the median time to relapse was only 5 (1.0–24) months. Therefore, haematopoietic stem cell transplantation (HSCT) is recommended for consolidation therapy in patients with CR after Venetoclax-based treatment; however, most of these patients are ineligible for HSCT due to their old age or poor performance status.…”
Section: Discussionsupporting
confidence: 64%
“… 3 Finally, although the majority of newly diagnosed patients respond to venetoclax-based combinations, the median duration of response may only be approximately 12 months, which necessitates an understanding of how resistance evolves and how this can be targeted. 23 In our study, we also found that four of 10 CR/CRi patients relapsed, and the median time to relapse was only 5 (1.0–24) months. Therefore, haematopoietic stem cell transplantation (HSCT) is recommended for consolidation therapy in patients with CR after Venetoclax-based treatment; however, most of these patients are ineligible for HSCT due to their old age or poor performance status.…”
Section: Discussionsupporting
confidence: 64%
“…This practice may tend to abandon these drugs, but in less advanced diseases, they may act better. However, the registration of many new drug trials is limited to morphological relapse (>5% fibroblasts) [ 52 ]. The response rate to new therapeutics may be higher if tested in MRD cases, and MRD is the only evidence of disease.…”
Section: Discussionmentioning
confidence: 99%